The Impact of AI on Human Resource Digital Transformation Salary Management - Utomo, Laksanto (Journal of Global Economy, Business and Finance, 2025)
The integration of Artificial Intelligence (AI) in compensation management represents a significant advancement in Human Resources (HR) digital transformation. This paper explores the multifaceted impact of AI on compensation management, highlighting its role in enhancing efficiency, accuracy, and strategic decision - making. Through a comprehensive review of current literature and case studies, we analyze how AI - driven tools and technologies are reshaping compensation strategies, contributing to overall organizational success.